The role of process innovation between organizational capability and software project success in Malaysian public sector - Rozaida, M. D.; Mahanum, Daim (Academic Research Publishing Group, 2018)
This study used the partial least square (PLS) and structural equation modeling (SEM) tool to examine factors influencing the process innovation of the organization capability in public sectors. It also measures the impact of process innovation on the success of software project process. Statistical results confirm that coordination of expertise, communication plan and IT infrastructure reach impact on process innovation while process innovation in turn positively influences the success of software project success. The result, besides indicating the suitability of the PLS in statistical analysis, has also contributed to a better understanding of the success of the software project process. Findings are useful for IT Managers and practitioners to improve the success of software project in Malaysian public sectors. Limitation and suggestion for future research are also included.